Association between MIS-C and Functional Gastrointestinal Disorders in Children: A Cross-Sectional Study - Uygun, Hatice; Yavuz, Sibel; Şahin, Tarık; Erdem, Nurettin; Turgut, Mehmet (Journal of Pediatric Infectious Diseases, 2023)
Objective Multisystem inflammatory syndrome in children (MIS-C) is a serious complication of coronavirus disease 2019 which causes a hyperinflammatory syndrome that can affect all organ systems. Functional gastrointestinal disorders (FGIDs) are a heterogeneous disease spectrum with unclear etiology. Today, it is known that low-grade inflammation can cause FGIDs. Our aim in this study was to investigate whether there is a higher frequency of FGID in children diagnosed with MIS-C.Methods In this study, 48 pediatric patients diagnosed with MIS-C were evaluated for functional gastrointestinal diseases according to the Rome IV criteria at least 6 months after diagnosis. The control group consisted of 61 pediatric patients without any chronic disease.Results In our study, the overall prevalence of FGIDs was 54.1% (n = 26) in the patient group and 22.9% (n = 14) in the control group. The difference between the groups was statistically significant (p < 0.001). The frequencies of undiagnosed abdominal pain, irritable bowel syndrome, constipation, and dyspepsia were 41.6% (n = 20), 12.5% (n = 6), 8.3% (n = 4), and 6.2% (n = 3) in the patient group, respectively. In the control group, the corresponding rates were 9.8% (n = 6), 3.2% (n = 2), 4.9% (n = 3), and 4.9% (n = 3), respectively. A significant difference was observed between the patient and control groups in terms of functional abdominal pain (p < 0.001).Conclusion The overall frequency of FGIDs and the prevalence of functional abdominal pain were higher in MIS-C patients than in control subjects. The data from this study support the hypothesis that FGIDs are more common in patients diagnosed with MIS-C than in healthy controls.
Keywords: children; functional gastrointestinal disorders; MIS-C; pediatric; Rome IV